(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
This article examines a sustainable architectural tradition embodied in the formation of the Bale Tengah within the Tenganan Pegeringsingan community in Bali. The Bale Tengah has been selected for its distinctive symbolic role in representing the conception of the life cycle within the broader framework of Tenganan’s belief system. The study seeks to establish a connection between vernacular architectural forms and practices, the sustainable utilization of natural resources, and the continuous assurance of equitable access to these resources for the community across generations. On one hand, the research investigates deeply embedded and well-practiced belief systems, such as the krama adat’s collective codes, social mores, and ethical values. On the other hand, it analyzes five determining elements of architectural formation symbolism, form, structure, construction, and the materials employed. A qualitative methodology has been adopted, combining subjective interpretation with empirical field research. Data collection was undertaken through a series of architectural documentations and in-depth interviews involving key community figures and krama adat village leaders. The findings reveal that although the term “sustainability” is absent from the Tenganan Pegeringsingan vocabulary, the community’s traditional dwelling embodies the essence of sustainable practice. Both the conception and construction of the Bale Tengah reflect a philosophy of safeguarding the future by maintaining social cohesion and ensuring the conservation of natural resources. This process historically rooted and self-reflective has played a crucial role in sustaining the endurance and continuity of the Tenganan Pegeringsingan community.